Randomized Comparison of Two Spacer Devices in Subjects with Reversible Airflow Limitation - Fred W Clarke; Leslie L Montgomery; David G Stubbing (Canadian Respiratory Journal)
OBJECTIVE: To assess a new spacer device. the ACE. by comparing it with the Aerochamber in subjects with reversible airflow limilation and assessing the change in lung function after inhaled bronchodilator.